Examining job characteristics, reward and recognition, work-life balance toward employee engagement among generation Y - Umikalsom, Omar (2016)
The main aim of this research was to examine the relationship on the factors contributing to the employee engagement among Generation Y, namely; job characteristics, reward and recognition, and work-life balance. The study focused at the employee engagement as an essential and critical aspect in determining and affecting sustainability and success of the company, as it is much relies on its main asset that is the employees. Data were gathered using questionnaires from the respondents who were generation Y employees in the PC Company located at Kuala Lumpur City Centre (KLCC). This study adopted SSPS in analyzing data. The results discovered that job characteristics, reward and recognition, and work-life balance were significantly correlated and contributed to the employee engagement. The study will also benefit the human resource practitioners theoretically and practically by providing direction and suggestions in formulating, designing and implementing the right policies, reward and recognition package and job design for PC Company. Likewise, limitation and recommendations for future research direction were also deliberated in this study.